Multisystem Inflammatory Syndrome In Children An Emerging Clinical Challenge For Pediatric Cardiac Surgery In The COVID 19 Era:Case Series - Cebeci, Halil; Altun, Dilek; Bingol, Demet Altun; Ozgen, Serpil Ustalar (LIPPINCOTT WILLIAMS \& WILKINS, 2024)
18th World Congress of Anaesthesiologists, Singapore, SINGAPORE, MAR 03-07, 2024